A memória narrada por jovens do ensino médio na significação do patrimônio cultural - Castro, José Valter (2017)
This study aimed to analyze the memories narrated by young people in high school on cultural heritage significance. To this end, it was necessary to identify the narratives produced by students on a selected heritage in your community; evidencing the collective memories present on done narratives productions and thus understand how young people mobilized the collective memories and school knowledge in the productions about the cultural heritage. These narratives in the form of an album were produced by young people who participated in the heritage education and artistic Project, being constituted as a mediation element to the analysis of the memories, meant in the cultural patrimony elected as memorable in the produced narratives. This study guided by qualitative research approach in education, in the form of case study. It was analyzed four albums produced in the project EPA, in 2015, by young people of State High School Castro Alves, in the city of Adustina-BA. Analyzing the narratives produced by young people was evidenced that the elements of the collective memory are present on it and reveal the social memory constituent of the various groups as historic heritage structure. The results were organized in shafts; taking into account these elements become almost irreducible on solidification of memory. The narrative about the heritage Boqueirão Farm depicts memories about the making of the work, the suffering and the survival of the country person. The narrative about regional handicrafts refers to memories present in everyday objects and sharpen an aesthetic look and arts of doing (crafts). And a third narrative, the albums Vieiras´ Chapel and Senhor do Bonfim Church, is marked by the elements present in a religious memory so present and intense in the country people and blessed relationship. The results show that the meanings attributed to the haritage are related to memory produced collectively in the course of time. Course that becomes effective in zone of culture and persists as identification in what is memorable and what constitute them as belonging to a collectivity.